Preparation and Structure Analysis of Three New Copper Complexes of Mellitic Acid With 4, 4′‐Bipyridine and 1, 3‐bis(4‐pyridyl)Propane. Issue 3 (18th January 2018) - Shimpi, Manishkumar R.; Giri, Lopamudra; Pedireddi, Venkateswara Rao
Abstract: Coordination complexes, [Cu2 (H2 L )( bpy )2 ]⋅2H2 O, (1 a ), [Cu(H3 L )2 (H2 O)4 ]⋅(H2 bpypa ) 2 ⋅6H2 O, (2 a ) and [Cu(H3 L )4 ][Cu(H2 O)6 ]⋅(H2 bpypa )4 ⋅20H2 O, (2 b ), of mellitic acid, H6 L, with 4, 4′‐bipyrdine, ( bpy ), and 1, 3‐ bis (4‐pyridyl)propane, ( bpypa ), have been prepared and the three‐dimensional structures are established by single crystal X‐ray diffraction unequivocally. The complex 1 a was prepared following hydrothermal method, while the complexes 2 a and 2 b were obtained concomitantly from an aqueous solution at room temperature. In the crystals of 1 a, both acid and the aza‐donors form coordination bonds with metal ions, while in 2 a and 2 b coordination bonding prevails between metal and acid molecules only, with aza‐donor molecules remain intact without coordinating to metal species. Further, 1 a and 2 b are noted to be yielding a host‐guest network, whereas 2 a forms planar sheets that are stacked in three‐dimensional arrangement. Abstract : The coordination polymers resulting from 1, 2, 3, 4, 5, 6‐benzenehexacarboxylic acid, H6 L, with Cu(II), in the presence of flexible bipyridyl ligands (4, 4′‐bipyridine and 1, 3‐ bis (4‐pyridyl)propane), have been reported. The study demonstrates the utilization of both coordinate bond as well as hydrogen bonds in the preparation of coordination assemblies.